On the Magnitude of the Geographic Distance Effect on Primary Agricultural and Processed Food Trade. Issue 2 (26th August 2014) - Ghazalian, Pascal L.
ABSTRACT The empirical trade literature regularly emphasizes the essential role of the geographic distance in determining the levels and patterns of international trade. This paper examines the diversities in the magnitude of the geographic distance effects on primary agricultural trade and on processed food trade between OECD countries. The empirical results from different specifications of the gravity model reveal the existence of significant variations in the magnitude of the distance effects on primary agricultural trade and on processed food trade over time and through economic, geo‐economic, and socio‐economic characteristics of the exporting and importing countries. These findings imply that disregarding the variations through the distance effect by relying on overall estimates would adversely affect the design of trade policies, and would limit the understanding of trade patterns.